Factors Associated With Subjective Musculoskeletal Disorder (MSD) Complaints Among Fitness Instructors In Semarang City, 2025 - Vimelani Afiska Mayratnaprima; Ratih Pramitasari (Journal Occupational Health Hygiene and Safety, 2026)
instructors due to repetitive movements, high physical load, and prolonged teaching duration. This study aimed to analyze factors associated with subjective MSD complaints among fitness instructors in Semarang City in 2025. A quantitative cross-sectional study was conducted with 110 instructors selected by accidental sampling. Data were collected using the Standardized Nordic Questionnaire (SNQ) and Rapid Entire Body Assessment (REBA). Bivariate analysis used Spearman Rank, Chi-square, and Fisher Exact tests (α=0.05). The prevalence of MSD complaints was 98.2% in the last 12 months and 97.3% in the last 7 days. There was no association between working period and MSD complaints (p=0.914; p=0.060). Working duration (p<0.001; p=0.017) and working posture (p<0.001; p<0.001) were significantly associated with MSD complaints, while exercise type was not (p=0.281; p=1.000). Strong correlations were observed for working duration (r=0.686) and working posture (r=0.763). Managing teaching duration and improving ergonomic posture are recommended to reduce MSD risk.